Programs for cheap! - Hackett, Jennifer; Hutton, Graham (2015)
Write down the definition of a recursion operator on a piece of paper. Tell me its type, but be careful not to let me see the operator’s definition. I will tell you an optimization theorem that the operator satisfies. As an added bonus, I will also give you a proof of correctness for the optimisation, along with a formal guarantee about its effect on performance. The purpose of this paper is to explain these tricks.